The Effect Of Hospital Management Information Systems On Human Resources Services In Haji General Hospital Medan, Sumatera Utara Province - Siregar, Sori Tua; Badaruddin; Andayani, Lita Sri Andayani (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Utilizing information technology by hospital human resources is essential for improving the efficacy and efficiency of hospital service administration. This study examines some variables in the management information systems on human resources services at Haji General Hospital Medan in Sumatera Utara Province using quantitative research methods with an associative research approach. The method is employed to identify the relation between some variables. This study has three independent variables: utilization of management information systems, satisfaction with information system use and ease of use of information systems. Meanwhile, the dependent variable is human resources services. Tests were conducted to evaluate the impact of independent factors on RSU Haji Medan's human resources services, individually and collectively. This study finds that each independent variable had a substantial effect on human resources services at RSU Haji Medan. Furthermore, the combination of these elements has a significant impact on human resources services at RSU Haji Medan.